The Handbook of Neuromodulation, (2 Volume Set): Volume 1 - Majumdar, Pritam; Fenoy, Albert J.; Matis, Georgios; Ozturk, Sait (Nova Science Publishers, Inc., 2022)
This book contains details of neuromodulation therapies including medical management and surgical management. This book will be very helpful for upcoming neurosurgeons, neurologists and neuromodulation specialists for conducting treatment properly and understanding the basic mechanisms of neuromodulation therapies. So far, many books have been published on this topic but this book contains all information on neuromodulation therapies and their approaches for upcoming clinical research and future directions for neurological surgery. This book has a total of 43 chapters which are written by global neuromodulation experts, neurosurgeons, neurologists and neuroscientists. These chapters are based on the authors’ expertise and experiences, and the editors of this book are all well-known experts. In one sentence, this book will be the handbook for upcoming doctors in these fields. © 2022 by Nova Science Publishers, Inc.